The effect of light-limitation on spinescent structural defence and its implications on resistance to herbivory in the shade - Adams, Ismat (Department of Biological Sciences, 2015)
Plants can resist herbivore pressure through structural or chemical defence or both. The ultimate goal of defence against herbivory is to reduce the amount of damage to biomass, but more specifically to protect against damage to meristematic tissue. The defences employed depend on the type of herbivory experienced, which is contingent on the herbivore and its mouthparts. This investigation was concerned with structural defence presented by spines. This type of defence protects against mammalian herbivores such as browsers. Spiny species do not dominate in low-light deep forest environments. Therefore the aim of this study was to determine the constraints on spines as a defence strategy under shaded conditions by assessing the effect of reduced light on spine efficiency. Spine efficiency was defined as the amount of defence afforded the plant given the resources available. Spines require carbon to be built and need to be arranged properly in order to present an adequate defence. Thus two non-mutually exclusive hypotheses were proposed: Light limitation reduces the ability of spines to present an adequate defence against browsers due to the architectural strategy employed and/or its influence on carbon gain. The spinescent plant chosen for study was Carissa macrocarpa (Ecklon) A.DC. Light condition of plants was determined using hemispherical photography. Spine efficiency of sun and shade plants was determined using a bite test and was evaluated using architectural and physiological analyses. Architectural analysis involved identifying levels of organisation within the plant across ontogeny and indentifying sun and shade growth strategies. Physiological analysis involved determining carbon gain of sun and shade individuals using gas-exchange measurements, as well as the measurement of biomass allocation by harvesting and oven drying different plant parts. Results showed that biomass allocation patterns of C.macrocarpa did not change in sun and shade but total biomass increased from shade to sunlit conditions. Architectural analysis revealed that in the sun the plant adopted a stout dense structure with high spine efficiency, while in the shade it was more elongated with lower spine efficiency. Therefore C.macrocarpa adapts to the light environment by adopting either the shade or the sun architectural strategy. The way in which this works is that light affects carbon gain, which either increases or decreases biomass and in turn leads the plant to adopt the sun or shade architectural strategy. The architectural strategy affects spine efficiency such that plants in the sun have higher spine efficiency than plants in the shade. Thus, spinescent plants do not do well in light limited environments because they are architecturally constrained to elongate in such conditions. This constraint would put them at higher risk of browser damage than plants in light-sufficient conditions, ultimately decreasing their fitness. If the patterns observed in C. macrocarpa prove to be general, then it helps to explain why spiny plants are more commonly found in open, sunlit environments than in deep shade.